Repercussions of the agri-food crisis at local and regional level - Akhvlediani, Tinatin,Gökten, Meryem,Marcinkowska, Izabela,Klakla, Jan Bazyli,Agostinelli, Delia (European Committee of the Regions, 2022)
This report aims to assess, in qualitative and quantitative terms, how the Russian invasion of Ukraine is affecting the EU countries and regions that are among the most impacted by the consequences of the war. Among the most negatively affected countries and regions, the study reviews Poland and Spain by taking into account (i) the border with Ukraine and Russia; (ii) their reliance on food supplies from Ukraine and/or Russia; and (iii) their vulnerability to increasing inflation due to supply shortages. As for the most resilient countries, we consider Hungary and Germany, based on their strong local production levels and low dependency on imports from Ukraine and Russia.
10.2863/47797
Keywords: Graue Literatur; Amtliche Publikation; Agraraußenhandel; Agrarproduktion; Ernährungssicherung; Lebensmittelmarkt; Krieg; Russisch; Ukrainisch; EU-Staaten; Deutschland; Polen; Spanien; Ungarn; agricultural market; agricultural situation; agricultural product; agricultural production; agri-foodstuffs; crop production; Ukraine; EU Member State; report